Need for Early Interventions in the Prevention of Pediatric Overweight: A Review and Upcoming Directions - Anne M. Dattilo; Leann Birch; Nancy F. Krebs; Alan Lake; Elsie M. Taveras; Jose M. Saavedra (Journal of Obesity)
Childhood obesity is currently one of the most prevailing and challenging public health issues among industrialized countries and of international priority. The global prevalence of obesity poses such a serious concern that the World Health Organization (WHO) has described it as a “global epidemic.” Recent literature suggests that the genesis of the problem occurs in the first years of life as feeding patterns, dietary habits, and parental feeding practices are established. Obesity prevention evidence points to specific dietary factors, such as the promotion of breastfeeding and appropriate introduction of nutritious complementary foods, but also calls for attention to parental feeding practices, awareness of appropriate responses to infant hunger and satiety cues, physical activity/inactivity behaviors, infant sleep duration, and family meals. Interventions that begin at birth, targeting multiple factors related to healthy growth, have not been adequately studied. Due to the overwhelming importance and global significance of excess weight within pediatric populations, this narrative review was undertaken to summarize factors associated with overweight and obesity among infants and toddlers, with focus on potentially modifiable risk factors beginning at birth, and to address the need for early intervention prevention.